THE EFFECT OF BUDGET RATIONALIZATION ON THE WORK PROGRAM OF KONI BENGKULU PROVINCE IN 2020 - Dendi Afrizal; Ahmad Soleh; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2020)
The rationalization of Budget will affect all department and the department who create work program for year 2020, the rationalization of budget also conducted by Bengkulu province government where the budget is more focused to prevent Corona virus so the assigned budget for official activities become less. It also impacts the KONI activity in Bengkulu Province, so the work programs at KONI Bengkulu province are delayed or not executed yet. The rationalization of budget has influence for work program at KONI in Bengkulu province, it is shows from simple linear regression analysis Y = 2.631 + 0.846X with X variable regression coefficient 0.846 also constanta 2.631, it is proved with hypothesis with tsig< tα, it is 0.000 < 0.05. from the test, it shows that correlation coefficient rvalue = 0.714. this value shows that the correlation between budget realization with work program is very strong because it has correlation value close to 1. So it can be concluded that budget rationalization has strong correlation with work program at KONI in Bengkulu Province. From hypothesis test, the tsig variable value is 0.000. this value if compared with tα=0.05 so tsig<tα(0.000<0.05).